Clinical effect of auricular point pressing with beans combined with acupoint massage in the treatment of post-stroke constipation with Qi deficiency syndrome (耳穴压豆联合穴位按摩治疗中风后气虚便秘的效果观察) - LI Chenchen (李陈晨); YANG Yu (杨宇); FAN Yan (范艳); JIA Tieying (贾铁英); HU Shirong (胡世荣) (Association of Integrative Nursing, 2021)
Objective To explore the effect of auricular point pressing with beans combined with acupoint massage in the treatment of post-stroke constipation with Qi deficiency syndrome. Methods Totally 120 patients with post-stroke constipation of Qi deficiency syndrome were randomly divided into control group and study group, with 60 cases in each group. The control group was given oral administration of rhubarb and sodium bicarbonate tablets, while the study group received auricular point pressing with beans combined with acupoint massage. The curative effect of intervention was evaluated, and the Traditional Chinese Medicine (TCM) syndrome integrals of constipation, quality of life score and satisfaction with nursing service were compared between two groups . Results The total effective rate in the study group was significantly higher than that in the control group(P＜0. 05). TCM syndrome integrals of constipation in the study group were lower than those in the control group after intervention(P＜0. 05). The score Patient Assessment of Constipation Quality of Life scale (PAC-QoL) dropped in both two groups after intervention, and score of PAC-QoL in the study group was lower than that in the control group (P＜0. 05). The total rate of patient satisfaction in the study group was higher than that in the control group (P＜0. 05). Conclusion Auricular point pressing with beans combined with acupoint massage therapy is effective to improve the clinical symptoms of patients with post-stroke constipation of Qi deficiency syndrome. (目的 探讨耳穴压豆联合穴位按摩治疗中风后气虚便秘的效果。方法 选取2020年1月-2021年2月医院收治的120例中风后气虚便秘患者, 依据随机数字表法分为对照组和研究组, 各60例。对照组给予口服大黄碳酸氢钠, 研究组给予耳穴压豆联合穴位按摩治疗。评价2组干预效果, 对比2组中医证候积分、生活质量评分及对护理的满意度。结果 研究组总有效率高于对照组, 差异有统计学意义(P＜0. 05)。干预后, 研究组患者便秘症候评分低于对照组(P＜0. 05)。2组患者生活质量评分较治疗前得到改善, 且研究组改善情况优于对照组(P＜0. 05)。研究组患者总满意高于对照组, 差异有统计学意义(P＜0. 05)。结论 对于中风后气虚便秘患者, 耳穴压豆联合穴位按摩可以有效改善患者的临床症状, 提升临床治疗效果, 提升患者对护理的满意度。)